DEVELOPMENT OF ECOLOGY-BASED JOURNALISM TEACHING MATERIALS: VALIDITY AND FEASIBILITY ON EKOSASTRA.COM - Ayu Nadira Wulandari; Yuliana Sari; Nadia Amelia Elyana Poluan (Jurnal Ilmiah Bina Bahasa, 2026)
This research aims to develop and evaluate ecology-based journalistic teaching materials, supported by the Ekosastra.com website, for the Indonesian Literature Study Program. The research is motivated by the gap in documentation between ecological journalism pedagogy and teaching materials. The research and development (R&D) approach was used in this study, guided by the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research involved 42 students in the needs analysis and 20 students in the limited implementation trial. The instrument was validated using a 1-4 Likert scale. The novelty of this research lies in combining an authentic digital platform with a domain-specific digital platform (Ekosastra.com) and teaching journalistic and ecological literacy. This has not been previously studied in Indonesian higher education. The results showed that the six-unit teaching materials received very valid ratings from the content experts (M=3.62) and media experts (M=3.54), and very good ratings from the students (M=3.48), all far above the minimum feasibility threshold. The teaching materials are a replicable model for integrating ecological literacy, journalism practice, and digital competence into the Indonesian Literature curricula, with broad implications for society 5.0-oriented higher education reform.